2014
DOI: 10.1002/cbic.201300726
|View full text |Cite
|
Sign up to set email alerts
|

Unique Crystal Structure of a Novel Surfactant Protein from the Foam Nest of the Frog Leptodactylus vastus

Abstract: Breeding by releasing eggs into stable biofoams (“foam nests”) is a peculiar reproduction mode within anurans, fish, and tunicates; not much is known regarding the biochemistry or molecular mechanisms involved. Lv‐ranaspumin (Lv‐RSN‐1) is the predominant protein from the foam nest of the frog Leptodactylus vastus. This protein shows natural surfactant activity, which is assumed to be crucial for stabilizing foam nests. We elucidated the amino acid sequence of Lv‐RSN‐1 by de novo sequencing with mass‐spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…High-resolution structural analysis of Ep-Rsn-2 and Lv-Rsn-1 by NMR and X-ray crystallography, respectively, revealed no structural similarities between the proteins ( Figure 3 D,E) 12 , 15 . Lv-Rsn-1 is a 23.5-kDa protein comprising two domains [12] . The N-terminal domain comprises a bundle of six antiparallel α helices.…”
Section: Stabilizing Frog Foam Nests With Ranaspuminsmentioning
confidence: 99%
See 3 more Smart Citations
“…High-resolution structural analysis of Ep-Rsn-2 and Lv-Rsn-1 by NMR and X-ray crystallography, respectively, revealed no structural similarities between the proteins ( Figure 3 D,E) 12 , 15 . Lv-Rsn-1 is a 23.5-kDa protein comprising two domains [12] . The N-terminal domain comprises a bundle of six antiparallel α helices.…”
Section: Stabilizing Frog Foam Nests With Ranaspuminsmentioning
confidence: 99%
“…In the past few years, the elucidation of high-resolution 3D structures of several surfactant proteins has opened the way for more detailed structure–function analysis of this exciting class of molecules 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 . These studies reveal that the mechanisms by which surfactant proteins achieve their function are highly diverse.…”
Section: Life At the Air–water Interfacementioning
confidence: 99%
See 2 more Smart Citations
“…fallax, Krintler, 1986), and the dermal glands of several species are known to produce defensive skin secretions (Cei et al, 1967), including antimicrobial peptides and other protein toxins found in L. fallax (Rollins-Smith et al, 2005;King et al, 2005a), L. labyrinthicus (Libério et al, 2014), L. laticeps (Conlon et al, 2009), L. latrans (Nascimento et al, 2004(Nascimento et al, , 2007Leite et al, 2010), L. pentadactylus (Habermehl, 1981;Barlow, 1998;King et al, 2005b;Limaverde et al, 2009;Sousa et al, 2009), L. syphax (Dourado et al, 2007). Similarly, the foam nests of L. vastus possess a novel surfactant protein (Hissa et al, 2008(Hissa et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%